Industrial‐scale vacuum casting with silicone molds: A review. Issue 1 (16th February 2022) - Wortmann, Martin; Frese, Natalie
Abstract: Vacuum casting (VC) of reactive polymer resins in silicone molds is one of the oldest rapid tooling methods. It is widely used in the industry for prototype and small‐series production of thermoset plastic parts. Despite its widespread use, its scientific exploration is still scarce compared to other prototyping methods, such as three‐dimensional (3D) printing. Compared to conventional 3D printing methods, a wide range of excellent material properties can be achieved, making it well suited for the production of functional prototypes and even final products. The properties of the thermosets are comparable to those of injection molding in terms of viable shapes, mold fidelity, and material properties. However, due to the high cycle time and limited service life of the molds, VC is rarely utilized for mid‐ or large‐series production. Here, we provide a comprehensive overview of the state of the art and recent advances in the field. The review also provides a detailed technical introduction to the mold production, the process flow, and the materials used. A particular focus is on the key challenges facing industrial‐scale VC today—how to reduce cycle time, and how to increase mold service life? Abstract : Vacuum casting (VC) with silicone molds is widely used industrially for prototype and small‐series production of thermoset plastic parts. Due to high cycle time and limited mold service life, VC is rarely utilized for mid‐ or large‐series production. Here, we review the state of the art and recent advances. The review provides technical introductions to mold production, process flow, and materials used. Further, we address the key challenges: reducing cycle time and increasing mold service life.